2023
DOI: 10.3390/genes14071450
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Genomic Healthcare Utilization, Patient Activation, and Intrafamilial Communication of Risk among Females Tested for BRCA Variants: A Mixed Methods Study

Abstract: This study aimed to gain a deeper understanding of genomic healthcare utilization, patient activation, and intrafamilial risk communication among racially and ethnically diverse individuals tested for BRCA variants. We employed an explanatory, sequential, mixed-methods study guided by the Theory of Planned Behavior. Participants completed an online survey, including sociodemographic, medical history, and several validated instruments. A subset of participants participated in in-depth, semi-structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We did not have sufficient variance in disagreement in assessment or either race or ethnicity to be able to investigate disparities in the tool’s performance. Multiple studies have found disparities in cancer genetics care based on race 48, 49 , ethnicity, and socioeconomic status 4 . While digital tools have potential to reduce disparities, care in their design, implementation, and evaluation is needed to ensure they perform and benefit patients equitably.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have sufficient variance in disagreement in assessment or either race or ethnicity to be able to investigate disparities in the tool’s performance. Multiple studies have found disparities in cancer genetics care based on race 48, 49 , ethnicity, and socioeconomic status 4 . While digital tools have potential to reduce disparities, care in their design, implementation, and evaluation is needed to ensure they perform and benefit patients equitably.…”
Section: Discussionmentioning
confidence: 99%
“…Two cases are presented using a qualitative, descriptive inquiry. Cases are drawn from a larger study that employed an explanatory sequential, mixed-methods approach to examine genomic healthcare utilization and intrafamilial communication of BRCA risk among ethnically and racially diverse individuals ( Hesse-Biber et al, 2023 ). The Boston College IRB approved the study (protocol #16.109.01) and participants provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…In-depth semi-structured interviews were conducted (SH-B) and transcribed verbatim (#011:04/27/2022, 73 min, ∼20,000 words; #003: 4/14/2022, 111 min, ∼16,000 words). Three investigators (SH-B, MS, AAD) conducted qualitative analysis on transcriptions as previously described ( Hesse-Biber et al, 2023 ). Two cases were purposefully selected from the larger sample as potential illustrations of identity theft.…”
Section: Methodsmentioning
confidence: 99%